Science And Religion: Quest For The Human Welfare - Mohd Ashraf Malik (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
August Comte in the 19th century, James Frazer and Sigmund Freud in the 20th century declared earnestly that religion will be superseded by science. Science according to them would explain everything that humanity would be confronted with in the future including purpose of life and the working of the universe. The global resurgence of religious movements since the 1970s, however surprised many such Euro-Western intellectuals who had assumed that the process of secularization, based on 19th and the 20th centuries positivistic ideas of progress and modernization, was universal, unidirectional, and inevitable. In their view all societies were moving relentlessly to increasingly secular conditions in which religious institutions would be progressively marginalized and their hold on society would diminish. The great Islamic Revolution of Iran (1979), the conversion of great number of non-Muslims to Islam since the momentous September 11, 2001 event and the proliferation of New Spiritualities the world over (21st century) astonished the scientists and secularists who could see religion dominating the human affairs defying all claims of science and ‘Enlightenment’ rationality. The renaissance of religion made many a men of intelligence to revisit the essence of religion. Like the scientists, Isaac Newton and Robert Boyle in the past, they began to see their work as the part of religious enterprise devoted to the understanding of God’s creation. In the paper my objectives would be aiming at identifying the prominent themes where science finds religion as complimentary and partner in furthering the cause of human welfare. The areas where religion (especially Islam), and science stand neutral towards one another may also be analysed. The research is primarily a library research analyzing narratives and arguments from selected religious and secular/scientific works.